2009
DOI: 10.1515/bot.2009.026
|View full text |Cite
|
Sign up to set email alerts
|

Checklist of benthic marine algae and cyanobacteria of northern Portugal

Abstract: The northern Portuguese coast is a biogeographic transition zone where many macroalgal species have their distribution limits; it is thus a particularly interesting region for investigating species distribution shifts. An updated and complete list of species for this region is not available in spite of its baseline importance for comparative studies with past and present data. Based on new records, literature references, and herbarium data, we provide an updated checklist of the benthic marine algae of the nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
53
1
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(64 citation statements)
references
References 40 publications
5
53
1
5
Order By: Relevance
“…This species is widely distributed, occurring not only all along Mediterranean (Flores-Moya et al 1989;Conde et al 1996;Bárbara and Cremades 1996;Babbini and Bressan 1997) and Atlantic (Guiry 1977;Neto 1994;Araujo et al 2009), where it has been extensively reported, but also in the Pacific (Abbott 1999;Lee 2008). It is a whitish-pink to reddish-lilac calcified algae, with articulated fronds and fish-bone-like arrangement.…”
Section: Introductionmentioning
confidence: 99%
“…This species is widely distributed, occurring not only all along Mediterranean (Flores-Moya et al 1989;Conde et al 1996;Bárbara and Cremades 1996;Babbini and Bressan 1997) and Atlantic (Guiry 1977;Neto 1994;Araujo et al 2009), where it has been extensively reported, but also in the Pacific (Abbott 1999;Lee 2008). It is a whitish-pink to reddish-lilac calcified algae, with articulated fronds and fish-bone-like arrangement.…”
Section: Introductionmentioning
confidence: 99%
“…Species with a southern, warm temperate, distribution were present further south, sometimes until Cape Verde (West Africa). Where no information was given in Lünning (1990), the distribution as determined by Gorostiaga et al (2004), Barbara et al (2005) and Araujo et al (2009) was adopted. Taxa were indicated as cosmopolitan whenever no clear restriction in distribution was found.…”
mentioning
confidence: 99%
“…The nonheterocystous cyanobacteria are, indeed, reported as the predominant forms in marine environments [3], [6], [43] and [46]. This seems to be also the case for Portugal, the Checklist of benthic marine algae and cyanobacteria of northern Portugal ("Checklist") reported 26 species of cyanobacteria, 15 of which are Oscillatoriales [2]. Strains belonging to the generaHyella, Myxosarcina, Lyngbya, Pseudophormidium and Calothrix were found in the same area (north of Portugal) as reported in the Checklist.…”
Section: Morphological Characterizationmentioning
confidence: 92%
“…In addition to their ecological importance, cyanobacteria are also recognized as being a prolific source of biologically active natural products; some of these compounds are toxic to a wide array of organisms [50]. Nevertheless, little is known about the diversity of these organisms along the Portuguese coast with only a few reports published [2] and [9]. Araújo et al [2] provided an updated checklist of the benthic marine algae of the northern Portuguese coast, including 26 species of cyanobacteria.…”
Section: It Is One Of the Warmest European Countries And Its Climatementioning
confidence: 99%
See 1 more Smart Citation